Case report: MicroRNA-10b as a therapeutic target in feline metastatic mammary carcinoma and its implications for human clinical trials - Savan, N. Anna; Saavedra, Paulo Vilar; Halim, Alan; Yuzbasiyan-Gurkan, Vilma; Wang, Ping; Yoo, Byunghee; Kiupel, Matti; Sempere, Lorenzo; Medarova, Zdravka; Moore, Anna (Frontiers in Oncology, 2022)
Ninety percent of deaths from breast cancer are caused by metastasis. miRNAs are critical players in biological processes such as proliferation, metastasis, apoptosis, and self-renewal. We and others have previously demonstrated that miRNA-10b promotes metastatic cell migration and invasion. Importantly, we also showed that miR-10b is a critical driver of metastatic cell viability and proliferation. To treat established metastases by inhibiting miR-10b, we utilized a therapeutic, termed MN-anti-miR10b, composed of anti-miR-10b antagomirs, conjugated to iron oxide nanoparticles, that serve as delivery vehicles to tumor cells in vivo and a magnetic resonance imaging (MRI) reporter. In our previous studies using murine models of metastatic breast cancer, we demonstrated the effectiveness of MN-anti-miR10b in preventing and eliminating existing metastases. With an outlook toward clinical translation of our therapeutic, here we report studies in large animals (companion cats) with spontaneous feline mammary carcinoma (FMC). We first investigated the expression and tissue localization of miR-10b in feline tumors and metastases and showed remarkable similarity to these features in humans. Next, in the first case study involving this therapeutic we intravenously dosed an FMC patient with MN-anti-miR10b and demonstrated its delivery to the metastatic lesions using MRI. We also showed the initial safety profile of the therapeutic and demonstrated significant change in miR-10b expression and its target HOXD10 after dosing. Our results provide support for using companion animals for further MN-anti-miR10b development as a therapy and serve as a guide for future clinical trials in human patients.